Emerging role of rhomboid family proteins in mammalian biology and disease - Landscheidt, Nina; Lemberg, Marius (Biochimica et biophysica acta. Biomembranes, 2013)
From proteases that cleave peptide bonds in the plane of the membrane, rhomboids have evolved into a heterogeneous superfamily with a wide range of different mechanistic properties. In mammals 14 family members have been annotated based on a shared conserved membrane-integral rhomboid core domain, including intramembrane serine proteases and diverse proteolytically inactive homologues. While the function of rhomboid proteases is the proteolytic release of membrane-tethered factors, rhomboid pseudoproteases including iRhoms and derlins interact with their clients without cleaving them. It has become evident that specific recognition of membrane protein substrates and clients by the rhomboid fold reflects a spectrum of cellular functions ranging from growth factor activation, trafficking control to membrane protein degradation. This review summarizes recent progress on rhomboid family proteins in the mammalian secretory pathway and raises the question whether they can be seen as new drug targets for inflammatory diseases and cancer. This article is part of a special issue entitled: Intramembrane Proteases.